Factors associated with high antibody titer following coronavirus disease among 581 convalescent plasma donors: A single-center cross-sectional study in Japan. Issue 2 (February 2022) - Suzuki, Tetsuya; Asai, Yusuke; Ide, Satoshi; Fukuda, Saori; Tanaka, Akihito; Shimanishi, Yumiko; Takahashi, Kozue; Terada, Mari; Sato, Lubna; Sato, Mitsuhiro; Inada, Makoto; Yamada, Gen; et al.
Abstract: Introduction: The ability to predict which patients with a history of coronavirus disease (COVID-19) will exhibit a high antibody titer is necessary for more efficient screening of potential convalescent plasma donors. We aimed to identify factors associated with a high immunoglobulin G (IgG) titer in Japanese convalescent plasma donors after COVID-19. Methods: This cross-sectional study included volunteers undergoing screening for convalescent plasma donation after COVID-19. Serum anti-severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) S-protein IgG antibodies were measured using a high-sensitivity chemiluminescence enzyme immunoassay. Results: IgG antibodies were measured in 581 patients, 534 of whom had full information of selected independent variables. Multiple linear regression analysis revealed that increasing age (1.037 [1, 025, 1.048]), days from symptom onset to sampling (0.997 [0.995, 0.998]), fever (1.664 [1.226, 2.259]), systemic corticosteroid use during SARS-CoV-2 infection (2.382 [1.576, 3.601]), and blood type AB (1.478 [1.032, 2.117]) predict antibody titer. Conclusion: Older participants, those who experienced fever during infection, those treated with systemic corticosteroids during infection, those from whom samples were obtained earlier after symptom onset, and those with blood type AB are the best candidates for convalescent plasma donation. Therefore, these factors should be incorporated into the screening criteria for convalescent plasma donation after SARS-CoV-2 infection.